The role of extracellular vesicles-derived microRNAs in the development of renal cell carcinoma - Venâncio, Patrícia Sofia Almeida (2023)
Renal cell carcinoma (RCC) is the most common and most lethal urological neoplasia amongst adults. In fact, approximately one-third of the patients are diagnosed with metastatic disease and approximately 20-30% will develop metastasis even after surgical nephrectomy. It is known that EVs play a crucial role in the tumour microenvironment establishment and are involved in the metastatic process. Thus, the aim of this study was to analyze an EV-derived miRNA profile associated with clear cell RCC (ccRCC) development and its role on the cell phenotype modulation. We analyzed a five-miRNA profile in EVs derived from tumoural RCC cell lines (tumoural vs normal) that represented different stages of ccRCC progression. We observed an increase in hsa-miR-571 and hsa-miR-3074-3p levels in EVs derived from metastatic cell line, FG-2, when compared to the control which led to a decrease in the RAD51mRNA expression levels. Additionally, we verified that the administration of EVs-FG-2 to the normal cell line led to a decreased cellular proliferation and migration of the recipient cell line. In conclusion, EVs-FG-2 carry hsa-miR-571 and hsa-miR-3074-3p acting as suppressors of tumour development.